Sports or/and Special Populations: Training Physiology in Health and Sports Performance - Aidar, Felipe (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Several factors have been identified as interfering with the success, rehabilitation, and fitness of athletes from childhood to adulthood, as well as in para-sport, and special populations, according to research. The performance and health of this population are affected by the relationships between stress, maturation, training load, and recovery. Environmental approaches aim to increase efficiency and physiological adaptations in this sense. In various situations and conditions, however, this stimulus-performance-adaptation relationship varies.As a result, we received contributions related (but not limited) to the following topics: training load monitoring; stress and physiological responses during exercise or sports; recovery process after exercise; changes after stress and/or training load; physiology of training in health and sports performance.